1987
DOI: 10.1016/0022-4731(87)90501-2
|View full text |Cite
|
Sign up to set email alerts
|

The heat-stable cytosolic factor that promotes glucocorticoid receptor binding to DNA is neither thioredoxin nor ribonuclease

Abstract: Treatment of rat liver cytosol containing temperature-transformed [3H]dexamethasone-bound receptors at 0 degree C with the sulfhydryl modifying reagent methyl methanethiosulfonate (MMTS) inhibits the DNA-binding activity of the receptor, and DNA-binding activity is restored after addition of dithiothreitol (DTT). However, transformed receptors that are treated with MMTS and then separated from low Mr components of cytosol by passage through a column of Sephadex G-50 have very little DNA-binding activity when D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Several other factors have been described that increase the DNA binding of activated glucocorticoid complexes. All of these factors are larger than our factor [i.e., ~72K (Payvar & Wrange, 1987), 70K (Tymoczko et al, 1988), 10-12K (Grippo et al, 1985;Tienrungroj et al, 1987b), and >5K (Schmidt et al, 1985;Harmon et al, 1988)], and none were isolated from crude nuclei. Small molecular weight substances, like /3-mercaptoethanol and Zn2+ (Sabbah et al, 1987), that increase the DNA binding of activated complexes cannot be our factor since these compounds would be included in Sephadex G-10 columns and since added thiols did not cause increased DNA binding (Table III).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Several other factors have been described that increase the DNA binding of activated glucocorticoid complexes. All of these factors are larger than our factor [i.e., ~72K (Payvar & Wrange, 1987), 70K (Tymoczko et al, 1988), 10-12K (Grippo et al, 1985;Tienrungroj et al, 1987b), and >5K (Schmidt et al, 1985;Harmon et al, 1988)], and none were isolated from crude nuclei. Small molecular weight substances, like /3-mercaptoethanol and Zn2+ (Sabbah et al, 1987), that increase the DNA binding of activated complexes cannot be our factor since these compounds would be included in Sephadex G-10 columns and since added thiols did not cause increased DNA binding (Table III).…”
Section: Discussionmentioning
confidence: 72%
“…Copyright. Published 1990 by the American Chemical Society been previously observed by us (Simons, 1977) and others (Tienrungroj et al, 1987b) that, under some conditions, more activated receptor-steroid complexes bind to nuclei than to DNA. The initial purpose of the present study, therefore, was to resolve the differences between nuclear and DNA binding of activated glucocorticoid complexes.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Indeed, protection of Trx1 against MMS-induced DNA damage could have been involved in DNA repair as redox signalling has been shown to affect APE1/Ref1 function, an apurinic/apyrimidinic endonuclease in the DNA base excision repair pathway (38,39), and APE1/Ref1 was shown to regulate the p53/p21 system (37,40). In addition, it was reported that the heat-stable cytosolic factor that promotes glucocorticoid receptor binding to DNA after MMS treatment is neither thioredoxin nor ribonuclease (41), suggesting that Trx1-mediated protection against MMS-induced DNA damage might be specific through certain cellular factors.…”
Section: Resultsmentioning
confidence: 99%
“…This would imply that an inhibitor to DNA binding is present in the cytosol of aged rats. Alternatively, one cannot dismiss the possibllty that an enhancer to binding exists in the young cytosols(38,84).A series of mixing experiments examining whether or not this putative inhibitor could negatively influence DNA binding in other vitamin D receptor preparations would be useful. Secondly, the detection of two protein bands at 52K and 50K spe cific for the kidney receptor was unexpected.…”
mentioning
confidence: 99%